Design and Validation of an Improved Rotational Variable Stiffness Mechanism - Carl Nelson; Kasey Moomau; Yucheng Li (Machines)
In various aspects of robotics, including human–robot interaction, the ability to dynamically adjust the apparent stiffness of an interaction (e.g., between the robot and its environment or between the robot and its payload) has become an important capability. Various means have been developed in recent years to achieve this, notable among them the so-called variable lever devices. In this paper, we present a new variable lever mechanism based on a gear–rack pair. This unique design combines the functionality of the lever itself with that of the stiffness-adjustment transmission. We show through simulations and hardware experiments the relatively large resulting range of achievable stiffness adjustment and efficient operation.